Akuntansi Manajemen Lingkungan dan Inovasi pada Perusahaan Peserta Proper di Provinsi Lampung - Destia Pentiana (Jurnal Ilmiah ESAI, 2016)
This study aims to know (a) the influence of environmental management accounting on process innovation, and (b) the influence of environmental management accounting on product innovation. This research was conducted on 30 companies of PROPER participants in Lampung Province in the Green and Blue category, where the category means the company has done good environmental management in the company operation. The data collection in this research was carried out through field study by using questionnaire. Further, the data were analyzed using simple regression analysis. The results of the research show that environmental management accounting significantly influenced the process of innovation, but environmental management accounting did not significantly affect the product innovation. Keywords: Environmental Management Accounting, Innovation, Process, Product